Implementation of Multicultural Education in the Gendang Beleq Extracurricular Activity at Sman 4 Mataram - Inni Khaerunnisa’; Rahmawati; Lian Kamila fitri; Idayanti; Dony Jayeswara; Dio Wira Winanja; Sawaludin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Multicultural education is education that is intended to instill a sense of tolerance, respect for different backgrounds among people. Multicultural education aims to build students' attitudes and knowledge through understanding diversity. At SMAN 4 Mataram, this education is implemented through the extracurricular Gendang Beleq, a traditional Lombok art. The research method used is a qualitative approach with data collection through observation, interviews, documentation. This research aims to explore the implementation of multicultural education in the Gendang Beleq extracurricular and identify the challenges faced. The research results show that this extracurricular is one of the milestones in implementing multicultural education because it can integrate cultural values, social values and the value of togetherness or mutual cooperation for students. However, in its implementation there were several obstacles experienced such as a lack of understanding of culture, lack of supporting resources, limited student interest and even cultural stereotypes among students.